Reinforcing capability of multiwall carbon nanotubes in alumina ceramic hybrid nanocomposites containing zirconium oxide nanoparticles. (November 2019) - Ahmad, Iftikhar; Islam, Mohammad; Parvez, Shahid; AlHabis, Nuha; Umar, Adeel; Munir, Khurram S.; Wang, Nannan; Zhu, Yanqiu
Abstract: In this study, we investigate the reinforcing capability of multiwall carbon nanotubes (mwCNT) in alumina (Al2 O3 ) ceramic hybrid nanocomposites containing zirconium oxide nanoparticles (ZrO2 np). For this purpose, highly dense hybrid nanocomposites containing well-dispersed ZrO2 np (8 vol%) and mwCNT (4 vol%) were fabricated by the hot-pressing method. The resulting hybrid nanocomposite exhibited a ten-fold finer microstructure and 116% enhanced fracture toughness as well as 12% greater hardness over the benchmarked monolithic Al2 O3 . The superior mechanical performance of the hybrid nanocomposite was attributed to the synergistic role of ZrO2 np and mwCNT in refining the matrix microstructure and inducing unique toughening mechanisms of micro-cracking by ZrO2 np and pull-out as well as crack-bridging by mwCNT. Qualitative and quantitative approaches were utilized to assess the individual and collective role of the reinforcing constituents in enhancing the performance of hybrid nanocomposite. The qualitative analysis by electron microscopes demonstrated strong interfacial adhesion of both reinforcing constituents with the based Al2 O3 matrix. Furthermore, the quantitative analysis verified that the enhanced mwCNT/Al2 O3 interfacial shear strength is caused by the intricate physical arrangement of the mwCNT within the matrix grains besides their chemical bonding at the interface. The role of fine-grained microstructure in establishing idiosyncratic mwCNT interlocking with the Al2 O3 matrix grains was meticulously investigated. Moreover, the influence of mwCNT/matrix interlocking on the mwCNT reinforcing ability and toughening mechanisms efficiency in the hybrid nanocomposite is discussed. Highlights: Al2 O3 /CNT/ZrO2 hybrid nanocomposites were prepared by hot-pressing technique. A 10 fold fine-grained microstructure was obtained for hybrid nanocomposites. The hybrid nanocomposites showed 116% better fracture toughness over Al2 O3 . Reinforcing capability of the CNT in hybrid nanocomposite was gauged.